Platform for entrepreneurship - Foix, Eduardo; Wielandt, Josefina (Base Diseño e Innovación, 2015)
Codelco’s subsidiary is an incubator of Chilean ventures based on the use of copper. Its model implies providing technological, methodological and development support to business ideas that have potential to reach the national and international markets and improve the daily life of the people.